Tissue microarray: physical and chemical parameters involved in the construction of recipient blocks - Marcos P. Santos; Thaiane A. Robeldo; Edwin David Castañeda; Ana Carolina Pagliarone; Karina N. Z. Pinto; Ricardo C. Borra (Sociedade Brasileira de Patologia Clínica, 2017)
ABSTRACT Introduction: Tissue microarray (TMA) is considered an innovative method in several fields, with a great diversity of applications and advantages over traditional histomorphometric techniques. The most important advantage that TMA offers is the simultaneous evaluation of a large number of specimens from a limited source of material. However, TMA exhibits a high rate of non-viable samples in the final stages of the process, which compromise their use in analyzes that can not be repeated. Objective: Considering this disadvantage, the objective of this study was to optimize the methodology to maximize the viability of the samples, as well as to increase the efficiency of the technique. Material and methods: For this purpose, several variables involved in the construction of the recipient blocks, including paraffin composition, diameter, spacing distance, localization and type of the tissue samples in the block were tested in order to establish correlations between the quality of the values and the parameters studied. Results: The results showed that the blocks built with polymer-enriched paraffin, subjected to the fusion protocol at 37ºC, associated to a tempering, and constructed with one millimeter diameter samples and 1000 µm spacing between tissues, produced slides whith superior features. Conclusion: The data obtained from the physical and chemical adjustments of the TMA recipient blocks provided vital information that, when applied in TMA research projects, may reduce the losses associated with the method.